Commitment of the Regional Government of East Seram Regency to Prepare the Draft of Regional Regulation Concerning CSR - Mahrita Aprilya Lakburlawal; Nancy Silvana Haliwela; Theresia Louize Pesulima (Fakultas Hukum Universitas Bhayangkara Jakarta Raya, 2024)
This research analyzes the commitment of the East Seram Regency Government preparing the Draft Regional Regulation (Ranperda) on Corporate Social Responsibility (CSR). This study is crucial considering the presence of companies in the region that have obligations to implement corporate social responsibility. Government supervision, through local government, will provide optimal impact for efforts to realize the improvement of community welfare, so it will not trigger disputes between communities and oil and gas mining companies in the region, due to neglected fulfillment of surrounding community rights resulting from oil and gas mining management. The research method used a qualitative approach with data collection techniques through interviews, observation, and documentation study. The results showed that the readiness of the East Seram Regency Government to prepare regional regulations for supervising oil and gas mining management activities in the region is marked by initiating meetings with various companies located in East Seram Regency and establishing the formulation of East Seram Regency Regional Regulation on CSR as a priority agenda to be proposed in the draft regional regulation this December with prioritized enactment in 2025.